DESCRIPTION OF TAFSIR SALMAN’S: A DISCOURSE ANALYSIS OF THE TAFSIR OF SCIENCE - El Rahma, Vicky Izza; Saniyah, Hulliyatus (Universitas Nurul Jadid, 2023)
This paper describes the pros and cons of the interpretation of ‘ilmi Salman ITB. The debate about the interpretation of 'Salman ITB's science has never ended, especially among Qur'anic scholars, until the question arises first which scientific understanding can only be justified from the Qur'an or an understanding of the Qur'an that encourages scientific research? Then according to Gusmian the first question has been the most dominant so far. The purpose of this paper is to respond to a controversy over the interpretation of 'ilmi Salman ITB. This paper is in the form of a literature review using qualitative methods with the type of discourse analysis research according to Teun A. Van Dijk. The results of this study are. There are differences of opinion about the existence of this interpretation of 'Salman ITB's science, that is, there are groups who agree and reject and are moderate. The Qur'an and science are both continuous in which the Qur'an itself is a guide for humans which contains many things including science or science. Text analysis according to Van Dijk is a discourse that is not enough to analyze texts and understand events, but also needs to analyze how the discourse develops.